1907
DOI: 10.1113/jphysiol.1907.sp001196
|View full text |Cite
|
Sign up to set email alerts
|

On the elimination of sulphocyanates from the blood, and their supposed formation in the salivary glands

Abstract: THE presence in saliva of a substance giving a red colour with ferric chloride was discovered by Treviranus1. Tiedemann and Gmelin2 proved later that this substance was a sulphocyanate. Since that time it has been found by numerous observers to be a frequent but not constant constituent of human saliva, and an occasional constituent of the saliva of the dog. Moreover its presence has been demonstrated in otber parts of the organism; thus Leared3, Gscheidlen4, and others found it in the urine, Leared in the blo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1933
1933
2006
2006

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Corper (1915) showed that [SCN-] in the fluids of lungs, eyes, kidneys and heart was similar to plasma [SCN-I. De Souza (1906), however, found that plasma SCN-also passes into glandular organs such as the salivary gland and the pancreas, while others found that it enters into the stomach (Kaltreider et al 1941) and red blood cells (Crandall and Anderson 1934;Gregersen and Stewart 1939 0.007 i 0.000 0.007 i 0.001 0.006 f 0.001…”
Section: Body Mass Changesmentioning
confidence: 99%
“…Corper (1915) showed that [SCN-] in the fluids of lungs, eyes, kidneys and heart was similar to plasma [SCN-I. De Souza (1906), however, found that plasma SCN-also passes into glandular organs such as the salivary gland and the pancreas, while others found that it enters into the stomach (Kaltreider et al 1941) and red blood cells (Crandall and Anderson 1934;Gregersen and Stewart 1939 0.007 i 0.000 0.007 i 0.001 0.006 f 0.001…”
Section: Body Mass Changesmentioning
confidence: 99%